Taxonomy of Centropomus Lacépède, 1802 (Perciformes: Centropomidae), with focus on the Atlantic species of the genus - de Figueiredo-Filho J.M. (2021)
Centropomus Lacépède, 1802 comprises 13 species of the fishes popularly knows as snooks, distributed in both Atlantic and Pacific coasts of America. Despite several studies on the group, conflicting taxonomic classifications still exist, including overlapping diagnostic characters, rendering species diagnoses extremely difficult. Herein, we review the taxonomy of Centropomus to elucidate species identities, redefine their diagnoses and to assess interspecific relationships based on the examination of 376 specimens. The study included complementary approaches, as analyses of external morphologic characters, linear and geometric morphometrics, and molecular analyses. Forty-nine characters were used for external morphology, 17 discrete plus 32 linear measurements. Shape and size were analyzed through geometric morphometrics of 185 specimens in lateral view. Partial sequences of the gene cytochrome c oxidase I were obtained for 129 specimens representing 11 species. Based on the consistent results retrieved from the morphologic and molecular analyses, we recognized six species of Centropomus from the Atlantic coast (C. ensiferus, C. irae, C. parallelus, C. pectinatus, C. poeyi and C. undecimalis). Centropomus mexicanus is treated as a junior synonym of C. parallelus. Six species from the Pacific coast are also tentatively recognized (C. armatus, C. medius, C. nigrescens, C. robalito, C. unionensis, and C. viridis), however further studies on the Pacific species are still needed. Information on type material, diagnosis, distribution, and taxonomic comments are provided for each species. An identification key to the species of Centropomus is presented. Copyright © 2021 Magnolia Press